Methodologic Framework For Military Capability Assessment of Armed Forces of the Czech Republic - Zdeněk Petráš (Vojenské rozhledy, 2017)
The article thematically relates to the completed analyses of national planning processes and NATO/EU defence planning processes. The aim of the article is to present a synthesis of findings from both analyses and their application while conceiving a proposal of methodology for military capability assessment of Armed Forces of the Czech Republic. The proposed approach to capability assessment stems from principles of the NATO´s J-DARTS (Joint Defence Planning Analysis and Requirements Tool Set) and EU´s SAEP (Scrutinising, Assessing, Evaluating and Prioritising Process) when the main attention was focused on the phase of matching current capabilities of force units against capability requirements, follow-on identification of shortfalls and their prioritisation. The degree of priority should primarily qualify the level of operational risk stemming from potential engagement of force units in an operation. It should be said that this concern is, together with respective phases of the capability planning process, the subject of the ongoing research.